Gambaran Retikulosit Ibu Nifas Kurang dari 25 Hari di Puskesmas Wonokerto 1 Kabupaten Pekalongan - Subur Wibowo; Erfitriyani Erfitriyani (Jurnal Medika Husada, 2024)
The postpartum period is the bleeding period after delivery and lasts for six weeks. Bleeding remains one of the three leading causes of maternal death in developed and developing countries. This research aimed to describe reticulocyte levels in postpartum mothers less than 25 days postpartum at Wonokerto 1 Health Center, Pekalongan Regency. This descriptive study used saturated sampling, collecting data from 25 postpartum mothers in May-June 2023. Results showed 32% of samples had high reticulocyte levels, while 68% had normal levels. This indicates that most postpartum mothers had normal erythropoiesis responses. The findings contribute to postpartum care improvement and anemia prevention strategies.